(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
Mamlakatimizda tariхan qisqa davr ichida inson, uning manfaatlari, huquq va erkinliklari oliy qadriyat hisoblangan huquqiy demokratik davlat, adolatli fuqarolik jamiyatini barpo etish borasida ulkan ishlar amalga oshirildi. Xususan, inson huquq va erkinliklarini muhofaza qilishning ishonchli kafolati bo‘la olgan “xabeas korpus” tizimida ham muhim ishlar amalga oshirildi. Quyidagi maqolada “xabeas korpus” nima ekanligi, uning maqsadi va vazifalari to‘g‘risida so‘z boradi. In our country, in a historically short period of time, great work has been done to establish a legal democratic state and a just civil society, in which a person, his interests, rights and freedoms are considered the highest value. In particular, important works have been carried out in the system of "habeas corpus", which can be a reliable guarantee of the protection of human rights and freedoms. The following article discusses what "habeas corpus" is, its purpose and functions.